The Impact of Moderate Chronic Hypoxia and Hyperoxia on the Level of Apoptotic and Autophagic Proteins in Myocardial Tissue. (16th August 2018) - Gyongyosi, Alexandra; Terraneo, Laura; Bianciardi, Paola; Tosaki, Arpad; Lekli, Istvan; Samaja, Michele
Abstract : The redox imbalance and the consequent oxidative stress have been implicated in many pathological conditions, including cardiovascular diseases. The lack or the excess of O2 supply can alter the redox balance. The aim of the present study was to understand the heart responses to prolonged hypoxia or hyperoxia and how such situations may activate survival mechanisms or trigger cell death. Seven-week-old Foxn1 mice were exposed to hypoxia (10% O2 ), normoxia (21% O2 ), or hyperoxia (30% O2 ) for 28 days, then the heart tissue was excised and analyzed. The alterations in redox balance, housekeeping protein levels, and autophagic and apoptotic process regulation were studied. The D-ROM test demonstrated an increased oxidative stress in the hypoxic group compared to the hyperoxic group. The level of hypoxia inducible factor-1 (HIF-1 α ) was increased by hypoxia while HIF-2 α was not affected by treatments. Chronic hypoxia activated the biochemical markers of autophagy, and we observed elevated levels of Beclin-1 while LC3B-II and p62 were constant. Nevertheless, we measured significantly enhanced number of TUNEL-positive cells and higher Bax/Bcl2 ratio in hyperoxia with respect to hypoxia. Surprisingly, our results revealed alterations in the level of housekeeping proteins. The expression of α -tubulin, total-actin, and GAPDH was increased in the hypoxic group while decreased in the hyperoxic group. These findings suggest that autophagy is induced in the heart under hypoxia, which may serve as a protective mechanism in response to enhanced oxidative stress. While prolonged hypoxia-induced autophagy leads to reduced heart apoptosis, low autophagic level in hyperoxia failed to prevent the excessive DNA fragmentation.